REPRESENTATION OF IMAGE GAMERS IN THE CHANNEL YOUTUBE GAME YOUTUBE COMPILATION VIDEO (Episode Pubg Indonesia - Voice To All 2.0, Pot Test 2.0, Epic Chicken Dinner) - Butar-Butar, Pandi Ahmad; Rimayanti, Nita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
YouTuber gaming is a phenomenon that is currently in high demand. In Indonesia, since 2015 until now the game creator content is developing rapidly. By displaying the interaction of gamers when playing games and gamers' behavior has been widely aired through online streaming media platforms such as YouTube so that it can be watched by many audiences. Milyhya is present as one of the creators of gaming content with the most viewers in Indonesia by presenting a new video game concept. Therefore, this study aims to find out how the representation of gamers' images in Milyhya youtube channel game compilation videos (Indonesian PUBG episode - Voice To All 2.0, Pan Test 2.0, Epic Chicken Dinner) through Roland Barthes semiotic analysis with Roland Barthes significance stage, denotation , connotations and myths. This study uses qualitative research with Roland Barthes's semiotic analysis. The subject of the research are the scenes in the Milyhya video. The object of this research is milyhya audio and visual video. In this study using Observation Data Collection, Documentation and Library Study Techniques. To achieve the validity of the data in this study the authors used Triangulation. The results obtained are the meaning of denotation in the form of interaction between fellow gamers in the PUBG game play, the meaning of connotations in the form of conversations and actions in the PUBG game play that depicts the lives of young people today in urban areas, and the mythical meaning in the form of community assumptions about the behavior of gamers. Representation of gamers 'images in Milyhya youtube channel game compilation videos (Indonesian PUBG episodes - Voice To All 2.0, Pan Test 2.0, Epic Chicken Dinner) then there are gamers' images as follows: likes to swear, friendly, loyal friends, ridiculing, clever foreign languages, teasers hypocritical, witty, likes to lie, arrogant, creative, problem solving, caring, afraid to lose, confident, clever. Keywords: Gamers, PlayernUnknown’s BattleGround’s, Representation, Semiotics